2022
DOI: 10.1227/ons.0000000000000274
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Machine Learning–Based Automated Surgical Instrument Annotation Using Publicly Available Intraoperative Video

Abstract: BACKGROUND: Intraoperative tool movement data have been demonstrated to be clinically useful in quantifying surgical performance. However, collecting this information from intraoperative video requires laborious hand annotation. The ability to automatically annotate tools in surgical video would advance surgical data science by eliminating a time-intensive step in research. OBJECTIVE: To identify whether machine learning (ML) can automatically identify surgical instruments contained within neurosurgical video.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Intraoperative tool movement tracking data has been shown to be clinically useful in quantifying surgical performance. A study demonstrated that machine learning can be utilized to identify surgical instruments within endoscopic endonasal intraoperative video and increase access to this information of surgical performance [22]. Deep neural networks have also been used in analyzing the operative steps in laparoscopic sleeve gastrectomy, with a 85.6% accuracy validated against surgeon annotations of the videos [23].…”
Section: Intraoperative Video Recording In Otolaryngology Education: ...mentioning
confidence: 99%
“…Intraoperative tool movement tracking data has been shown to be clinically useful in quantifying surgical performance. A study demonstrated that machine learning can be utilized to identify surgical instruments within endoscopic endonasal intraoperative video and increase access to this information of surgical performance [22]. Deep neural networks have also been used in analyzing the operative steps in laparoscopic sleeve gastrectomy, with a 85.6% accuracy validated against surgeon annotations of the videos [23].…”
Section: Intraoperative Video Recording In Otolaryngology Education: ...mentioning
confidence: 99%
“…[6][7][8] Within Neurosurgery, our group demonstrated that neural networks could reliably detect surgical instruments in view in a cadaveric training exercise and that these results translated to real intraoperative video. 9,10 The use of time series deep learning approaches extends to efforts outside of the analysis of surgical video, such as measuring intracranial pressure. 11,12 We wholeheartedly concur with Dr Lim's view that, despite the widespread availability of modeling approaches, exploiting intraoperative time series data remains an undiscovered scientific frontier with deep clinical applications.…”
mentioning
confidence: 99%
“…6-8 Within Neurosurgery, our group demonstrated that neural networks could reliably detect surgical instruments in view in a cadaveric training exercise and that these results translated to real intraoperative video. 9,10 The use of time series deep learning approaches extends to efforts outside of the analysis of surgical video, such as measuring intracranial pressure. 11,12…”
mentioning
confidence: 99%
“…7-9 Subsequently, 3 intraoperative endoscopic endonasal videos from YouTube (YouTube; Google LLC) were used to test the detector and demonstrate its generalizability. Markarian et al 6 concluded that surgical instruments contained within the endoscopic endonasal intraoperative video were able to be detected using a fully automated ML model. They also noted that although multiple data sets from disparate contexts were not beneficial in improving the model and its tool detection, it may potentially improve the generalizability of the model for alternative use.…”
mentioning
confidence: 99%
“…Furthermore, for many neurosurgeons, aiming to achieve technical excellence can be a significant contributor to their potential success. Models, such as the one produced by Markarian et al, 6 can provide objective and quantifiable measurements to assist in not only differentiating between experienced and inexperienced surgeons but also help residents and early surgeons improve their technical expertise. For machine learning models, operative videos can be a rich source of data for analyzing surgical performance and understanding technical skills.…”
mentioning
confidence: 99%